PENGARUH FREE CASH FLOW, PROFITABILITAS, DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2019-2022 - Soeiswanto, Chintya; Karamoy, Herman; Weku, Priscillia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2024)
The company must fulfill its dividend distribution obligations to shareholders, while still ensuring optimal operational continuity. A company's decision regarding the process of distributing profits, whether as dividends to shareholders or as retained earnings for future investments, is referred to as dividend policy. Some factors that can affect dividend policy are free cash flow, profitability, and liquidity. The purpose of this study is to determine the effect of free cash flow, profitability, and liquidity on dividend policy. This study used a sample of 44 food and beverage companies listed on the Indonesia Stock Exchange in 2019-2022. The method used is quantitative research with a purposive sampling technique. In this study, data were analyzed using multiple linear regression analysis. The results showed that free cash flow and profitability had a positive and significant effect on dividend policy, while liquidity has no effect on dividend policy.Keywords : Free Cash Flow, Profitability, Liquidity, Dividend Polic